Analisis Komparasi Potensi Kebangkrutan Dengan Menggunakan Metode Altman Z-Score, Springate, Dan Zmijweski Pada Perusahaan Pertambangan Sektor Batu Bara Yang Terdaftar Di Bei Tahun 2017-2019 - Alifia Nuraini; Ronny Malavia Mardani; Budi Wahono (E-JRM : Elektronik Jurnal Riset Manajemen, 2020)
ABSTRACTThis study aims to compare the model prediction of bankruptcy in a company mining in the coal sector using the tool of bankruptcy prediction method is Altman's Z-Score, Springate, and Zmijweski on the industry of coal mining which listed in Indonesia stock exchange years 2017-2019, as well as to know the most accurate prediction of all three models of the bankruptcy. In this study, using 12 of a sample of companies from 22 populations on the company in the coal sector which is listing in BEI. make sample with certain criteria. the data used in the day this use the financial statements published on the stock exchange. the technique in comparing bankruptcy prediction models by using analysis of kruskal wallis. of the day this results in that there is a significant difference in predicting bankruptcy between 3 the model the results obtained sig of 0.000. the results rank the highest, namely the method of Altman Z-Score values obtained rank 75,97 the second is Zmijweski values obtained rank 46,39, and the third is Springate value rank 41,14.Keywoard: Bankruptcy, Prediction Models,Financial Statement